Asking for Change: Feasibility, acceptability, and preliminary outcomes of a manualized photovoice intervention with youth experiencing homelessness. (October 2017) - Bender, Kimberly; Barman-Adhikari, Anamika; DeChants, Jonah; Haffejee, Badiah; Anyon, Yolanda; Begun, Stephanie; Portillo, Andrea; Dunn, Kaite
Abstract: Photovoice is a participatory action research method that empowers participants to photograph their everyday lives as a means of documenting and advocating for their needs; it has rarely been utilized with young people experiencing homelessness. The current study examined the feasibility, accessibility, and preliminary outcomes associated with participation in Asking for Change, a manualized Photovoice intervention, among youth (ages 18–21) staying in a homeless shelter ( N  = 22). Multiple sources of data, including field observation, standardized pre-post measures, and qualitative exit interviews were collected across two cohorts of Asking for Change. Results suggest the intervention was feasible and highly acceptable to many young people, created new opportunities to connect with young people, and, among those surveyed pre and post intervention ( n  = 9), was associated with improvements in communication skills, social connectedness, resiliency, and well-being. This article discusses the challenges and benefits inherent in doing this work and outlines a robust research agenda to move this knowledge base forward. Highlights: Young people experiencing homelessness will participate in a photovoice project. Youth appreciate having a voice and partnering with adults and peers. Participation is associated with increases in social connectedness and resiliency. Community members attending photovoice exhibits gained empathy and awareness.